Prevalence of Fosfomycin Resistance and Mutations in murA, glpT, and uhpT in Methicillin-Resistant Staphylococcus aureus Strains Isolated from Blood and Cerebrospinal Fluid Samples - Fu, Zhuyingjie; Ma, Ying; Chen, Chunhui; Guo, Yan; Hu, Fupin; Liu, Yang; Xu, Xiaogang; Wang, Minggui (Frontiers in Microbiology, 2016)
In China, fosfomycin alone or in combination with other antibiotics is commonly used in the treatment of infections caused by Gram-positive bacteria, including methicillin-resistant Staphylococcus aureus (MRSA). Although fosfomycin-resistant S. aureus strains have continued to emerge and increase, the research on them is rare. In order to determine the prevalence and mechanisms of fosfomycin resistance in MRSA clinical isolates, a total of 96 non-duplicate MRSA isolates were collected from blood and cerebrospinal fluid samples at Huashan Hospital in Shanghai, China between 2004 and 2014. Antimicrobial susceptibility testing was performed by agar dilution. Meanwhile, the fosfomycin-resistance-related genes, fosB, murA, glpT, and uhpT, were amplified by PCR and subjected to sequencing analysis. Multilocus sequence typing (MLST) was conducted to assess strain types. The minimum inhibitory concentration (MIC) of fosfomycin for the 96 MRSA strains ranged from 1.0 to >1,024 mg/L, and approximately 70% (67/96) of the isolates were resistant to fosfomycin (MIC ≥ 64.0 mg/L). Nine isolates with MICs ≥ 128 mg/L carried fosB gene. Twenty-five distinct mutations were detected in the murA (7), glpT (10), and uhpT (8) genes. While five of the murA mutations and five of the glpT mutations were observed only in fosfomycin-sensitive isolates and one of the murA mutation was found both in fosfomycin-resistant and fosfomycin-sensitive isolates, the remaining 14 mutations (1 murA, 5 glpT, and all uhpT mutations) were present only in fosfomycin-resistant isolates. MLST analysis demonstrated that the majority (46/67) of the glpT and/or uhpT mutants belong to ST5, the predominant sequence type among the fosfomycin-resistant MRSA isolates. In conclusion, there is a high rate of fosfomycin resistance in MRSA strains. The mutations in the murA, glpT, and uhpT genes are common in fosfomycin-resistant MRSA strains, and may play a greater role in the development of fosfomycin resistance than the presence of the fosB gene in these organisms.